Budaya Keimaman Orang Kristen: Kajian Teologis dan Praktis Kehidupan Orang Kristen Masa Kini - Takimai, Naftali; Auwe, Daud (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2022)
This study aims to analyze the priestly culture of Christians today theologically and practically. The issue of the priestly function of Christians that has not been running well is a challenge for the lives of Christians today. This research uses a qualitative method with the type of literature study. The results of the study state that theologically, the text of 1 Peter 2:9 states the eternal existence of the priesthood of believers as a royal priesthood. This means that God guarantees the priesthood of believers with the intention that when God appoints His people as priests, He maintains the priesthood of His people, and He guides His people as priests in the present life and in the future.